Analisis Resepsi Penonton pada Karakter Tokoh dalam Film Teman Tapi Menikah 2 Karya Rako Prijanto pada Mahasiswa Pendidikan Bahasa Indonesia Angkatan 2021 - Muttalib, Abdul; Irmayani, Naim; Nurhashisya, Nurhashisya (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2023)
This research aims to analyze audience reception, especially Indonesian Language Education students class of 2021, towards the characters in the film "Teman Tapi Marikah 2". The research method used is qualitative with content analysis techniques, namely data collection through observation, interviews and questionnaires. The results of the research show that there are variations in interpretation and meaning of the characters Dito and Ayu, the main characters of the film. Some informants see Dito as a husband who is loving, loyal and humorous, while other informants see Ayu as a strong, independent and intelligent woman. This research can be concluded that the film "Teman Tapi Menikah 2" succeeded in presenting characters and stories that triggered various interpretations from the audience. This shows the richness of film as a communication medium that is able to convey different messages to each individual.